Waste Management in the European Union: A Case Study of Netherlands - Respatyo, Gth Hasto; Nugrahani, Henny Saptatia Drajati (Green Publisher Indonesia, 2025)
This Study aims to explore Waste Management Strategies in the European Union with examples of waste management implementation in Netherlands. In this study, a multydisciplinnary approach was carried out where waste management would be linked to the commitment of Dutch political parties in carring out regional cooperation related to waste management. EU member states agreed to cooperated on the Waste Prevention Programme (WPP). This study used qualitative methode with data sources from documents published by European Union and The Dutch government. In this Study, the concept of waste management was used. The findings of this study show that waste management in The European Union and its member states is carried out as an effort to achieve the sustainable Development Goals (SDGs). The results show that producers of goods produced in the European Union and their distributors are responsible for the abundance of waste from these products. Basic mechanisms of waste management in Europe, ranging from waste sorting, the use of renewable technology in waste management, and increasing recycling capacity. The conclusion that can be drawn from this study is the importance of waste management strategies for the European Union and its member states. In regional studies, social issues related to the environment such as waste management in Europe can be the subject of in-dept research that can be explored with a multidisciplinary approach and viewed from political perspective.